Design and Analysis of thermosyphon Solar Water Heating System. - Kakuru, Stephen (Kabale University, 2024)
In rural areas of Uganda, access to affordable hot water is a persistent challenge with communities often relying on firewood and charcoal for water heating which contributes to deforestation, air pollution, and health hazards hence respiratory diseases like asthma, lung cancer, TB, and allergic disease, climate changes and global warming. This research aimed at the design and analysis of a thermosyphon solar water heater that heats water using solar energy which is healthy, environmentally friendly, cost-effective, easily maintained, and simple since it depends on natural convection and gravity force for water flow. The system is made of a 4m2 flat plate collector to convert solar energy into thermal energy, an insulated stainless steel storage tank of 240 liters capacity for storing hot water, a pipe system for transporting water, and a painted mild steel frame for supporting the system. Various principles, assumptions, and formulae were used in the design of the system components to obtain the appropriate dimensions of parts and the best materials selected. The 3D modal of the system was made using SOLIDWORKS, imported into ANSYS workbench for thermal analysis, and solidworks2020 for fluid flow analysis, and then all results generated were well discussed.